Public Awareness on Cord Blood Banking in Saudi Arabia - Dunia Jawdat; Sulaiman AlTwijri; Hadeel AlSemari; Mayssa Saade; Ahmed Alaskar (Hindawi Limited, 2018)
Background. In the last decade, cord blood (CB) has proven to be a valuable source of hematopoietic stem cells for transplantation to treat many hematological disorders. Since then, many CB banks have been established worldwide. Our aim was to estimate the level of public awareness of CB banking in Saudi Arabia. Study Design and Methods. A self-administered questionnaire of 22 multiple choices was conveniently distributed, consisting of demographics, awareness measure, attitude toward banking preference, and donation for research data. Results. A total of 1146 participants have completed the questionnaire. The majority were young female 19-25 years old (26%), who are college graduates (57%) with middle class socioeconomic status (82%). The subjective assessment of the overall knowledge was inadequate (66%). For the objective assessment, 12 questions were asked about CB source, collection, storage, and usage. Only half of the subjects (52%) knew that CB is a source of stem cells. More than half did not know the main use of CB. About half did not know about the method of collection nor the condition of storing. Conclusion. This study shows a high lack of knowledge about CB banking. More than half of the subjects were unaware of CB banking and its uses. However, most subjects are accepting CB storage, which anticipates great impact and efficacy on educational programs. Moreover, the data demonstrated that health professionals were not the source of knowledge. We recommend having comprehensive educational campaigns with clear information about CB banking to facilitate positive perspectives towards donation and scientific research.